KADAR AIR DAN STABILITAS DIMENSI BERDASARKAN SUHU PENGERINGAN DAN JENIS KAYU (Moisture Content and Dimension Stability Based on the Temperature of Dry Kiln and Wood Types) - H.Usman, Fadillah (jurnal TENGKAWANG, 2011)
Wood drying is a process to remove water from the wood to stabilize the dimension. The research was to determine the level of dimension stability of wood in dependence of drying temperature and type of wood (Tectona grandis L.f and Paraserianthes falcataria L) for temperature drying there are three standard treatments: 50C, 70C and 90C. The parameter measured in this research is the dimensional stability of wood. Results show that the type of wood has a strong effect on stability dimension, while the dryng temperature and the interaction of both factors had no effect. Paraserianthes falcataria L wood best indicates the level of dimensional stability, with a mean value of depreciation ratio T/R of 0.99. The dimensional stability of Tectona grandis L.f, had a mean value of T/R 1.64 for T/R . Average wood density values in this study for Tectona grandis L.f was 0,65 g/cm3 and Paraserianthes falcataria L 0.42 g/cm3. The same type of wood from outside of West Kalimantan had a density equal the value of 0.67 g/cm3 and 0.33 g/cm3. This indicates that the origin of the timber had no effect on density and dimensional changes of the wood Key word: Moisture content, dimension, temperatur of the dry klin, wood type